Effect of Increased Ionic Liquid Uptake via Thermal Annealing on Mechanical Properties of Polyimide-Poly(ethylene glycol) Segmented Block Copolymer Membranes - ÇİFTÇİOĞLU, GÖKÇEN ALEV (MDPI, 2021)
Proton exchange membranes (PEMs) suffer performance degradation under certain conditions-temperatures greater than 80 degrees C, relative humidity less than 50%, and water retention less than 22%. Novel materials are needed that have improved water retention, stability at higher temperatures, flexibility, conductivity, and the ability to function at low humidity. This work focuses on polyimide-poly(ethylene glycol) (PI-PEG) segmented block copolymer (SBC) membranes with high conductivity and mechanical strength. Membranes were prepared with one of two ionic liquids (ILs), either ethylammonium nitrate (EAN) or propylammonium nitrate (PAN), incorporated within the membrane structure to enhance the proton exchange capability. Ionic liquid uptake capacities were compared for two different temperatures, 25 and 60 degrees C. Then, conductivities were measured for a series of combinations of undoped or doped unannealed and undoped or doped annealed membranes. Stress and strain tests were performed for unannealed and thermally annealed undoped membranes. Later, these experiments were repeated for doped unannealed and thermally annealed. Mechanical and conductivity data were interpreted in the context of prior small angle X-ray scattering (SAXS) studies on similar materials. We have shown that varying the compositions of polyimide-poly(ethylene glycol) (PI-PEG) SBCs allowed the morphology in the system to be tuned. Since polyimides (PI) are made from the condensation of dianhydrides and diamines, this was accomplished using components having different functional groups. Dianhydrides having either fluorinated or oxygenated functional groups and diamines having either fluorinated or oxygenated diamines were used as well as mixtures of these species. Changing the morphology by creating macrophase separation elevated the IL uptake capacities, and in turn, increased their conductivities by a factor of three or more compared to Nafion 115. The stiffness of the membranes synthesized in this work was comparable to Nafion 115 and, thus, sufficient for practical applications.
Keywords: copolymerization; bicontinuous structures; ionic liquids; polymer electrolyte membranes